THE RELATION OF STRESS WITH INSOMNIA TO ELDERLY - Shanti Rosmaharani; Deny Sriwidyastuti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Introduction: Stress is the most common problem faced by the elderly. Stress is a psychological disorder that can cause insomnia in the elderly. Insomnia can cause serious physical problems if not treated properly This study aims to determine the relation of stress with insomnia. Methods: The design of this study used correlational analytics with a cross-sectional approach. The population in this study were all the elderly in Serut Hamlet, amounting to 40 elderly, a large sample of 40 respondents, using total sampling. The independent variable is stress using the Kessler Psychological Distress Scale questionnaire and the dependent variable is insomnia using the Insomnia Rating Scale questionnaire. Data analysis using the Spearman Rank test with α = 0.05. Results: the statistical test obtained p = 0.000, which means that it is much smaller than the standard significance of 0.05 or (p α) with a correlation coefficient of 0.631. It means that there is the relation of stress with insomnia to elderly in the Serut village of Sukorame Lamongan, which is relatively strong. Discussion: Stress will affect the work of the hypothalamus in the brain precisely in the Supra Chiasmatic Nucleus which can result in disturbed sleep. Drink warm milk before going to bed, take a warm bath, soak feet with warm water, clean the bed, use aromatherapy if you like fragrances and listen to music to reduce stress that causes insomnia in the elderly.